A preliminary report on the rural changes in the savannah area of the Western State of Nigeria, with special reference to tobacco production. - Kranendonk, H. C. (Ibadan Nigerian Institute of Social & Economic Research, 1968)
Part I presents a brief historical outline and a summary of the principal stages of tobacco production, as well as a description of the organizational aspects of flue-cured tobacco production in the savannah area of W. Nigeria (Oyo and Ibarapa). In Part II the impact of tobacco growing in the area, and the changes that have taken place over the past 20 years, are discussed. Special attention is given to changes in agricultural practices; the functioning of the Flue-Cured Producers' Associations and farmers' attitudes towards them; the labour situation; and a UNESCO Adult Education programme especially tailored for the tobacco producers' associations. One chapter is devoted to the assessment of the place of food crops in the economy of the area. In Part III a number of factors are surveyed which have contributed to the growing importance of the area as a producer of a variety of agricultural products, and attempts to explain the successful adoption of tobacco by the local farmers. T. A.
Includes bibliographical references.
lje
Loans
Keywords: Tobacco production; Nigeria